Make a Move: A Multi-Method, Quasi-Experimental Study of a Program Targeting Psychosexual Health and Sexual/Dating Violence for Dutch Male Adolescents - Mirthe C. Verbeek; Daphne van de Bongardt; Maartje P. C. M. Luijk; Joyce Weeland (Youth, 2025)
Adolescent sexual and dating violence (SDV) is a worldwide problem. Although male adolescents in vocational education or youth care may be at increased risk of perpetrating SDV, little is known about effective gender-specific prevention. Therefore, we conducted a quasi-experimental evaluation of a Dutch group counseling program promoting psychosexual health and preventing SDV among male adolescents aged 12–18 years: Make a Move. The 66 participating male adolescents completed three questionnaires (baseline, post-test, 3-month follow-up; 48.5% retention). We also conducted interviews with a subsample of four adolescents and two program trainers and performed observations in one group. With these multi-method, multi-informant data, we evaluated program effectiveness on the six intended outcomes (attitudes, social norms, self-efficacy, skills, intentions, and SDV perpetration) by (1) statistically comparing self-reports between the intervention and control groups; (2) thematically analyzing interview data; and (3) describing three individual male adolescent cases, triangulating questionnaire, interview, and observation data. We found limitations in program integrity, evidence for program effectiveness on skills, and mixed evidence for effects on attitudes, but no evidence for effects on socials norms, self-efficacy, or SDV perpetration. Yet our interviews indicated perceived effectiveness on self-efficacy and intentions. We also found indications of adverse effects on attitudes and intentions. We offer suggestions for program refinement and future program evaluations.